ON THE COMPARATIVE EFFICIENCY OF TRAWLS MADE OF COTTON POLYETHYLENE AND COMBINATION OF BOTH THE MATERIALS. - KARTHA, R N; GEORGE, V C; RADHALAKSHMI, K (Fishery Technology, 2017)
The merits and demerits of cotton, polyethylene and combinationof the two materials ascertained on the basis of cost,wear and tear, maintenance, total catch and qualitative analy~isof the catch are discussed by making comparative fishingexperiments with the three trawl gears made of these materials.The study can be concluded with a suggestion for switchingover to polyethylene twisted monofilarnents for better, in caseof bottom trawls without in any way adversely affecting thecatch of shrimps and at the same time for enhanced fish catch.Eventhough the combination net is found to be equal inefficiency as the polyethylene net this idea cannot be convenientlyadopted from the point of view of economy.